2014
DOI: 10.1111/jfd.12324
|View full text |Cite
|
Sign up to set email alerts
|

The expression of selected genes linked to metabolic homeostasis in obese pansteatitis‐suffering Mozambique tilapia, Oreochromis mossambicus (Peters)

Abstract: The Oreochromis mossambicus (Peters) population inhabiting Lake Loskop, South Africa, is characterized by a high incidence of obesity and pansteatitis. We investigated potential links between the impaired health of Lake Loskop O. mossambicus and the endocrine system by assessing the expression of selected genes associated with the thyroid and adrenal endocrine axes as well as peroxisome proliferator-activated receptor gamma (pparg). Moreover, contaminant-induced thyroid and/or metabolic modulation in Lake Losk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 82 publications
(147 reference statements)
0
14
0
Order By: Relevance
“…However, condition factor was not a significant predictor of pansteatitis severity, supporting the findings of Truter et al . () who were unable to link the pansteatitis in Lake Loskop fish to abnormal obesity through hormonal disruption. However, a lack of any relationship between δ 15 N values (as an indicator of trophic level) and size or age does not support the notion of a shift towards piscivory with age as a systematic adaptive strategy of O. mossambicus .…”
Section: Discussionmentioning
confidence: 99%
“…However, condition factor was not a significant predictor of pansteatitis severity, supporting the findings of Truter et al . () who were unable to link the pansteatitis in Lake Loskop fish to abnormal obesity through hormonal disruption. However, a lack of any relationship between δ 15 N values (as an indicator of trophic level) and size or age does not support the notion of a shift towards piscivory with age as a systematic adaptive strategy of O. mossambicus .…”
Section: Discussionmentioning
confidence: 99%
“…Surface water treatments were constantly aerated, but WAF treatments were not. Tadpoles assigned to surface water were fed (∼70 mg of Sera Micron [Sera] per tank) throughout acclimation and exposures, seeing that fasting may alter the expression of thyroid‐linked genes and that the surface water samples likely contained algae and other microorganisms to forage on . The WAF–exposure tadpoles and fish were only fed during the acclimation period.…”
Section: Methodsmentioning
confidence: 99%
“…Other portions of the Olifants River system have similarly witnessed massive mortality events of crocodiles and fish. In 2008, approximately 180 adult crocodile carcasses were discovered in the Olifants River Gorge in Kruger National Park (KNP), some 530 km downstream from Lake Loskop, with an estimated number of 500 individual deaths in total [ 2 , 6 , 7 , 10 – 13 ]. The next season (2009), approximately 24 crocodile carcasses were observed in the same area [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond isolating and connecting specific point source(s) to the large-scale mortality events in the Olifants River system (2003–2010), veterinary examination concluded that the ultimate cause of death in these events was an environmental form of pansteatitis, a disease noted by the presence of inflammation in adipose tissue [ 11 , 14 ]. In addition to crocodile deaths, other species have presented pansteatitis and/or suffered mortality events, including the African sharptooth catfish ( Clarias gariepinus ), Rednose labeo ( Labeo rosae ), Mozambique tilapia ( Oreochromis mossambicus ) and serrated hinged terrapins ( Pelusios sinuatus ) [ 2 , 6 , 10 , 13 , 18 ]. Fish-eating waterfowl species in the Olifants River system have been affected as well; African fish eagles ( Haliaeetus vocifer ) in the Lake Loskop area have struggled to reproduce and cormorant numbers are on the decline [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation